Electronic structure of benzene adsorbed on single-domain Si(001)-(2 × 1): A combined experimental and theoretical study - Gokhale, S.; Trischberger, P.; Menzel, Dietrich; Widdra, Wolf; Dröge, H.; Steinrück, Hans-Peter; Birkenheuer, U.; Gutdeutsch, U.; Rösch, Notker (Journal of Chemical Physics, 1998)
Benzene adsorption on a single-domain Si(001)-(2 × 1) surface has been studied by thermal desorption spectroscopy (TPD) and angle-resolved photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. Angle-resolved photoemission spectra for the saturated benzene layer exhibit well-defined polarization and azimuthal dependencies compatible with a flat-lying benzene molecule with local C symmetry. Based on these results two structure models are proposed. First-principles density functional cluster calculations have been performed for each of these structures. Total energy minimization and a detailed comparison of the experimental ARUPS spectra with the one-particle spectra of the model clusters leads to a 1,4-cyclohexadienelike adsorption complex with a flat-lying benzene molecule which is di-σ bonded to the two dangling bonds of a single Si-Si surface dimer. Especially, one of the unoccupied 1e (π*) orbitals of the free benzene molecule shifts down (by about 3 eV) and evolves into the highest occupied molecular orbital (HOMO) of the chemisorbed molecule. © 1998 American Institute of Physics.